Disability and Fantasy in Rick Riordan’s Percy Jackson and the Olympians series - Pilling, Alexandra (Curtin University, 2020)
This research explores the question: how is disability constructed in contemporary works of junior fantasy fiction? This research seeks to identify ways in which the use of fantasy in Riordan’s junior fantasy series, Percy Jackson and the Olympians, can assist in challenging dominant social and cultural stereotypes of learning disabilities such as ADHD and dyslexia. This research includes a junior fantasy novella which draws upon themes uncovered by the research and analysis.